2002
DOI: 10.1007/s12110-002-1004-7
|View full text |Cite
|
Sign up to set email alerts
|

Height and reproductive success in a cohort of british men

Abstract: Two recent studies have shown a relationship between male height and number of offspring in contemporary developed-world populations. One of them argues as a result that directional selection for male tallness is both positive and unconstrained. This paper uses data from a large and socially representative national cohort of men who were born in Britain in March 1958. Taller men were less likely to be childless than shorter ones. They did not have a greater mean number of children. If anything, the pattern was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(123 citation statements)
references
References 26 publications
2
121
0
Order By: Relevance
“…In keeping with the distinction between luxury and necessity, the preference for this type of relationship is more common in middle-class and upper-middle-class Western cultures than in many other cultures (Hewlett, 1992) or in the work-fewer sexual partners than their more symmetric peers (Furlow, Armijo-Prewitt, Gangestad & Simpson, 2000;Manning, Koukourakis, & Brodie, 1997). Confirming that women's stated preferences are often put into practice, Phillips et al (2001) and Nettle (2002) found that physically smaller and less-robust men are less likely to be chosen as marriage partners than are taller and morerobust men.…”
Section: Personal and Behavioral Attributesmentioning
confidence: 99%
“…In keeping with the distinction between luxury and necessity, the preference for this type of relationship is more common in middle-class and upper-middle-class Western cultures than in many other cultures (Hewlett, 1992) or in the work-fewer sexual partners than their more symmetric peers (Furlow, Armijo-Prewitt, Gangestad & Simpson, 2000;Manning, Koukourakis, & Brodie, 1997). Confirming that women's stated preferences are often put into practice, Phillips et al (2001) and Nettle (2002) found that physically smaller and less-robust men are less likely to be chosen as marriage partners than are taller and morerobust men.…”
Section: Personal and Behavioral Attributesmentioning
confidence: 99%
“…Moreover, in most mammals body size has been shown to play a major role in acquiring mates and resources, as larger males are more likely to win fights (Lindenfors et al, 2007), and are more attractive to females (Charlton et al, 2007(Charlton et al, , 2012McElligott et al, 2001). In humans, taller men have been found to be healthier (La Batide-Alanore et al, 2003;Smith et al, 2000), enjoy higher reproductive (Nettle, 2002;Pawlowski et al, 2000), academic (Hensley, 1993) and socioeconomic (Harper, 2000;Judge and Cable, 2004) success, and are more attractive to Western women (Mautz et al, 2013;Stulp et al, 2014;Swami et al, 2008;Yancey and Emerson, 2014) than shorter men, despite possible costs associated with male tallness (i.e. energy allocation trade-off between growth and reproduction: see Pisanski and Feinberg (2013) for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Height has also been linked to marital and fertility outcomes in men. In Western populations, tall men have more marriages, are less likely to be childless and have more children than shorter men (Mueller and Mazur 2001;Nettle 2002;Pawlowski et al 2000), which ultimately leads to a positive correlation between height and reproductive success.…”
Section: Introductionmentioning
confidence: 99%